If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(x + 8) = 44 Reorder the terms: 2x + 3(8 + x) = 44 2x + (8 * 3 + x * 3) = 44 2x + (24 + 3x) = 44 Reorder the terms: 24 + 2x + 3x = 44 Combine like terms: 2x + 3x = 5x 24 + 5x = 44 Solving 24 + 5x = 44 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 5x = 44 + -24 Combine like terms: 24 + -24 = 0 0 + 5x = 44 + -24 5x = 44 + -24 Combine like terms: 44 + -24 = 20 5x = 20 Divide each side by '5'. x = 4 Simplifying x = 4
| 7x-2=10x+8 | | 16x^2+14x+49=52 | | 2t+3(t+2)=4 | | 45+15x=225 | | 34780=x-0.4x+10060 | | 2+2x=-6-2x | | 13-7x=-9x-13 | | 49=3(2c+-5)+4 | | 2(x+6)=18x+5x+38 | | 30m5/35m4 | | 9n^2+10n-8=0 | | 11x=363 | | -16x^2+96x+5=133 | | -1.333x+.83x+2=-.5+.166 | | 9x-80=15 | | 8-(x-3)+7=0 | | (x+3yi)=4i | | 2.2c+4.2c-6=c+7 | | -x-1=-4x-19 | | [(x-3)(x-3)]+[(y+4)(y+4)]=36 | | -x+5=3x-31 | | [(x-3)(x-3)]+[(y+3)(y+3)]=36 | | ax-bx+y=z | | ln(2x+5)=3.3 | | (x-6)x=247 | | 100-50x=(10-2x)(10-2x)(4-x) | | (3x-5)+x=(-x+15)+180 | | 2x^2+14x-44=0 | | 100-50x=(10-2x)2(4-x) | | abc*de=fghjk | | 140x+90y=690550 | | x-2=-2x+13 |